The Effect of Footwork Exercise On Agiility in Badminton Extracurricular Students at SMP N 1 BPR Ranau Tengah South Sumatera - Iyakrus, Iyakrus; Usra, Meirizal; Ramadhan, Arizky; Kurniawan, Apri (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
This study aims to determine the effect of footwork exercises on agility, this research method is an experimental study that uses a one group pretest-posttest design. Consisting of 20 samples who were given pretests first and then given 16 dive treatments after which a posttest was carried out to determine the improvement. The instrument test used is the agility T-Test. The population in this study were badminton extracurricular students at SMP Negeri 1 BPR Ranau. The sampling used is total sampling, where the number of samples is equal to the population. Based on the table above, it can be seen that the conclusion P (T<=t) of two tails is 0.0000. That means the value is significant 0.0000 < 0.05, so this result shows that there is a significant difference. Thus the alternative hypothesis (Ha) which reads "There is an effect of footwork exercises on the agility of students who take part in extracurricular training at SMP N 1 BPR Ranau Tengah Sumatera Selatan" is indicated a, so there is a significant difference in footwork exercises on agility in badminton extracurricular students at SMP Negeri 1 BPR Ranau.